A CLINICAL AND RADIOGRAPHIC ASSESSMENT OF THE EFFICACY OF THE LESION STERILIZATION AND TISSUE REPAIR TECHNIQUE (LSTR) IN PRIMARY TEETH - Gamasita, Natasha; Bramanti, Indra; Santoso, Aloysia Supartinah; Rifani, Rifani; Yunirahmilia, Yunirahmilia (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: Pulp infection in primary teeth is a frequent case found in the clinic and requires endodontic treatment. Root canal preparation of primary teeth is quite difficult because of the anatomic variations of the roots and the need to manage children’s behaviour during the treatment. The short and non-invasive treatment that is preferable for pediatric patients is lesion sterilization and tissue repair (LSTR) technique. Aim: This article aims to evaluate the efficacy of LSTR treatment in deciduous teeth. Methods: Electronic databases including PubMed and Google scholar were searched using PICO keywords. Relevant articles only in the English language and full text (in vivo studies and case reports) published from Januari 2013 to Juny 2023 were selected. Result: According to the collected information there were thirteen articles included in the inclusion criteria. LSTR technique in primary teeth has shown excellent rates of clinical success and good radiographic results. Conclusion: LSTR can be considered as a treatment option for pulpally involved primary teeth.